2008
DOI: 10.1002/art.23327
|View full text |Cite
|
Sign up to set email alerts
|

Coaching patients with early rheumatoid arthritis to healthy physical activity: A multicenter, randomized, controlled study

Abstract: A 1-year coaching program for healthy physical activity resulted in improved perceived health status and muscle strength, but the mechanisms remain unclear, as self-reported physical activity at healthy level did not change.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
150
0
6

Year Published

2010
2010
2014
2014

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 102 publications
(160 citation statements)
references
References 28 publications
(28 reference statements)
4
150
0
6
Order By: Relevance
“…Because exercises were thought to provoke joint damage by enhancing disease activity (2), patients with inflammatory arthritis, especially RA, were discouraged from performing weight-bearing exercises. In a previous randomized controlled trial (RCT), we showed that an exercise program had a greater impact on both disability assessed by the Health Assessment Questionnaire (HAQ) and quality of life than conventional joint rehabilitation (3), contrasting with most of the previous similar studies that failed to detect any statistical difference on the HAQ (4,5) or quality of life (6). Several trials showed that exercises were safe in RA rehabilitation and effectively improved aerobic fitness (3,5,7,8).…”
Section: Introductionmentioning
confidence: 97%
“…Because exercises were thought to provoke joint damage by enhancing disease activity (2), patients with inflammatory arthritis, especially RA, were discouraged from performing weight-bearing exercises. In a previous randomized controlled trial (RCT), we showed that an exercise program had a greater impact on both disability assessed by the Health Assessment Questionnaire (HAQ) and quality of life than conventional joint rehabilitation (3), contrasting with most of the previous similar studies that failed to detect any statistical difference on the HAQ (4,5) or quality of life (6). Several trials showed that exercises were safe in RA rehabilitation and effectively improved aerobic fitness (3,5,7,8).…”
Section: Introductionmentioning
confidence: 97%
“…So far, intervention studies of HEPA in RA have been evaluated in two randomized controlled studies with partially contradictory results. One study reported increased HEPA levels but no effects on health-related outcome [10], while the other found improvements in perceived health and muscle function without being able to demonstrate any change in HEPA levels [11]. Thus, the mechanisms behind the positive outcome were unclear and the providers´ coaching skills were not measured.…”
Section: Health-enhancing Physical Activitymentioning
confidence: 99%
“…Due to lack of research there is limited evidence as to whether many physiotherapy interventions have a beneficial effect (Vliet Vlieland 2007). However, regular physical exercise and encouragement to increase physical activity have been proven to be effective in decreasing symptoms in persons with RA (Brodin et al 2008). The described positive outcomes of regular physical activities are improved physical function including increased muscle strength and endurance, aerobic fitness, and joint range of motion, as well as reduction of pain and fatigue (Cairns and McVeigh 2009;Cooney et al 2011).…”
Section: The Role Of Physiotherapymentioning
confidence: 99%
“…Those positive effects of physical activities and regular exercise can enhance sexual health since the mentioned outcomes are affecting sexual health (Hill, Bird, and Thorpe 2003;Josefsson and Gard 2010). Physical activities can be coached directly by the physiotherapist in 2-3 sessions/week or by homebased programs where coaching is done by phone or by follow-up visits at the physiotherapy clinic (Brodin et al 2008). Pain is a prioritized outcome for persons with RA and pain often affects sexual health negatively.…”
Section: The Role Of Physiotherapymentioning
confidence: 99%
See 1 more Smart Citation